DEVELOPMENT OF LEARNING INSTRUMENTS OF PROBLEM BASED LEARNING INVOLVING MATHEMATICAL PROBLEM SOLVING ABILITY OF STUDENTS IN 8TH GRADE SMP/MTs FOR LINEAR SYSTEMS WITH TWO VARIABLES MATTER - Eva Novita Nurhasanah; Yenita Roza; Sehatta Saragih (Jurnal Prinsip Pendidikan Matematika, 2020)
Learning in the class must be well planned, one of which to create learning instruments that refer to the curriculum implementation. This research aims to produce mathematics learning instruments (Syllabus, Lesson Plan, and Student workshet) using the problem based learning model in the linear systems with two variables matter. This research is a research and development (R&D) using the 4-D model. The research instrument were an instrument of validity in the form of a validation sheet to assess the validity (syllabus, RPP and LKPD) and practical instruments in the form of a questionnaire for students' responses to LKPD. Validation data analysis results obtained an average value for the syllabus is 3.36 in the category of very valid, value for the RPP is 3.23 in the category of valid, value for the LKPD is 3.32 in the category very valid. Validation result facts state the syllabus, RPP and LKPD are feasible use. The results of practicality data analysis of LKPD in small group was 87.01% in the very practical category and the result of practicality data analysis in large group trials was 86.10% in the very practical category. Which means the mathematics learning instruments can improve students’ mathematical problem solving ability and feasible used for students in learning.